Impact of COVID‐19 pandemic on epilepsy care in Japan: A national‐level multicenter retrospective cohort study. Issue 3 (12th June 2022) - Kuroda, Naoto; Kubota, Takafumi; Horinouchi, Toru; Ikegaya, Naoki; Kitazawa, Yu; Kodama, Satoshi; Kuramochi, Izumi; Matsubara, Teppei; Nagino, Naoto; Neshige, Shuichiro; Soga, Temma; Takayama, Yutaro; et al.
Abstract: Objective: The impact of the coronavirus disease 2019 (COVID‐19) pandemic on epilepsy care across Japan was investigated by conducting a multicenter retrospective cohort study. Methods: This study included monthly data on the frequency of (1) visits by outpatients with epilepsy, (2) outpatient electroencephalography (EEG) studies, (3) telemedicine for epilepsy, (4) admissions for epilepsy, (5) EEG monitoring, and (6) epilepsy surgery in epilepsy centers and clinics across Japan between January 2019 and December 2020. We defined the primary outcome as epilepsy center‐specific monthly data divided by the 12‐month average in 2019 for each facility. We determined whether the COVID‐19 pandemic‐related factors (such as year [2019 or 2020], COVID‐19 cases in each prefecture in the previous month, and a state of emergency) were independently associated with these outcomes. Results: In 2020, the frequency of outpatient EEG studies (−10.7%, P  < .001) and cases with telemedicine (+2608%, P  = .031) were affected. The number of COVID‐19 cases was an independent associated factor for epilepsy admission (−3.75 × 10 −3 % per case, P  < .001) and EEG monitoring (−3.81 × 10 −3 % per case, P  = .004). Furthermore, a state of emergency was an independent factor associated with outpatient with epilepsy (−11.9%, P  < .001), outpatient EEG (−32.3%, P  < .001), telemedicine for epilepsy (+12, 915%, P  < .001), epilepsy admissions (−35.3%; P  < .001), EEG monitoring (−24.7%: P  < .001), and epilepsy surgery (−50.3%, P  < .001). Significance: We demonstrated the significant impact that the COVID‐19 pandemic had on epilepsy care. These results support those of previous studies and clarify the effect size of each pandemic‐related factor on epilepsy care.